Does market interaction erode moral values? - Björn Bartling; Ernst Fehr; Yagiz Özdemir (University of Zurich, Department of Economics, 2020)
The widespread use of markets leads to unprecedented material well-being in many societies. We study whether market interaction, as a side effect, erodes moral values. An encompassing understanding of the virtues and vices of markets, including their possible impact on moral values, is necessary to make informed decisions on the spheres in society where the allocation and incentive functions of markets should exercise their power, and where this may not be desirable. In a seminal and highly influential paper, Falk and Szech (2013) provide experimental data that seem to suggest that "market interaction erodes moral values." Although we replicate their main treatment effect, we show that additional treatments are necessary to corroborate their conclusion. These treatments, however, reveal that repeated play and not market interaction causes the erosion of moral values. Our paper thus shows that neither Falk and Szech's data nor our data support the claim that market interaction erodes moral values.
Keywords: C91; D02; D62; D63; 330; market interaction; moral values